A Test of the Alchian-Allen Conjecture with Transaction-level Trade Data - Choi, Jieun (Taylor and Francis, 2020)
We use Kosovo’s transaction-level import value, tariff duties and transport cost data for very finely disaggregated products to test the Alchian–Allen conjecture. First, we show that the elasticity of freight costs to import prices is much lower than the unitary elasticity predicted by the iceberg transport cost hypothesis. Second, we find that import unit values rise with transport costs and decline with ad valorem tariffs. Our results confirm the Alchian–Allen conjecture that per-unit transport costs reduce the price of high-quality varieties relative to low-quality varieties, raising their relative demand in high freight cost destinations.